IMPLEMENTATION OF GUIDED INQUIRY LEARNING MODEL ON THE TOPIC OF INVERTEBRATE TO ENHANCE STUDENT CURIOSITY AT GRADE X MIA - Ertando, Alfi; Prayitno, Baskoro Adi; Harlita, Harlita (Unnes Science Education Journal, 2019)
The research aimed to enhance student’s curiosity at grade X MIA by implementation of guided inquiry learning model on the topic of invertebrate. Research method was a Classroom Action Research based on the model developed by Lewin (1992). This research was performed within 3 cycles with implementation of guided inquiry learning model based on Kuhlthau (2010). The subject is grade X MIA consist of 17 men students and 22 women students. Data were obtained by questionnaire, interviews, documentation, and observation sheets of four aspects of curiosity developed by Daniel Berlyne (1960) consisted of epistemic curiosity, perceptual curiosity, specific curiosity, diversive curiosity. The result showed that the student’s curiosity in precycle: epistemic curiosity at 21% with very low category, perceptual curiosity at 8% with very low category, specific curiosity at 12% with very low category, diversive curiosity at 23% with very low category. The student’s curiosity in cycle I: epistemic curiosity at 22% with very low category, perceptual curiosity at 21% with very low category, specific curiosity at 28% with very low category, diversive curiosity at 28% with very low category. The student’s curiosity in cycle II: epistemic curiosity at 32% with low category, perceptual curiosity at 24% with very low category, specific curiosity at 35% with low category, diversive curiosity at 39% with low category. The student’s curiosity in cycle III: epistemic curiosity at 46% with medium category, perceptual curiosity at 42% with low category, specific curiosity at 42% with low category, diversive curiosity at 44% with medium category. The student’s curiosity increased from very low category (16%) in precycle becomes low category (43,5%) in cycle III and meet the target research. Based on the results of research can be concluded that guided inquiry learning model can improve students' curiosity.